Association between length of hospital stay and fractures in the spine, pelvis, and lower extremity among patients after intentional fall from a height: an analysis of the Japan Trauma Databank - Daizoh Saitoh; Yoshihiro Tanaka; Takero Terayama; Hiroyuki Toda; Aihide Yoshino; Masanori Nagamine (Trauma Surgery & Acute Care Open, 2023)
Objective This study investigated the association between the number of regions with fractures in the spine, pelvis, and lower extremity (NRF) and the proportion of patients with a length of hospital stay (LOS) ≥30 days among those who attempted suicide by falling from a height.Methods Data recorded between January 1, 2004 and May 31, 2019 in the Japan Trauma Databank of patients aged ≥18 years injured by suicidal falls from a height and with ≥72 hours of LOS (period from admission to discharge home or to another hospital) were analyzed. Patients with an Abbreviated Injury Scale score ≥5 in the head region or those who died after admission were excluded. Multivariate analyses including clinically relevant variables as covariates were performed to determine the association, expressed as risk ratio with 95% CI, between NRF and LOS.Results Among 4724 participants, the multivariate analysis revealed significant factors related to LOS ≥30 days, including NRF=1 (1.64, 95% CI 1.41 to 1.91), NRF=2 (2.00, 95% CI 1.72 to 2.33), NRF=3 (2.01, 95% CI 1.70 to 2.38), systolic blood pressure in the emergency department (ED; 0.999, 95% CI 0.998 to 0.9997), heart rate in the ED (1.002, 95% CI 1.00 to 1.004), Injury Severity Score (1.007, 95% CI 1.00 to 1.01), and intubation in the ED (1.21, 95% CI 1.10 to 1.34). However, history of psychiatric diseases was not a significant factor.Conclusion An increase in NRF was associated with an increase in LOS of patients injured by intentional falls from a height. This finding can help both emergency physicians and psychiatrists in acute care hospitals to develop better treatment strategies with attention to time constraints. Further investigation of the association between LOS and both trauma and psychiatric treatment is required to evaluate the effect of NRF on treatment in acute care hospitals.Level of evidence Level III, retrospective study with up to two negative criteria.